SCIENTIFIC AND METHODOLOGICAL FOUNDATIONS FOR THE DEVELOPMENT OF PEDAGOGICAL COMPETENCE OF FUTURE TEACHERS BASED ON ELECTRONIC EDUCATIONAL RESOURCES - Ganiev Shahzod Ravshanbekovich (International Scientific and Current Research Conferences, 2023)
This article explores the scientific and methodological aspects of the development of pedagogical competence of future teachers, with an emphasis on the use of electronic educational resources. In the context of the modern educational environment, saturated with information and technological innovations, the authors consider the role of electronic educational resources in the formation of professional skills and knowledge of future teachers. The article highlights the theoretical and methodological aspects of pedagogical competence, describes the advantages of using electronic educational resources in the context of training future teachers. The authors consider practical methods and strategies that contribute to the effective use of electronic educational resources for the development of pedagogical competence.